2017
DOI: 10.1002/jcc.24851
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped C60 as a robust catalyst for CO oxidation

Abstract: The O activation and CO oxidation on nitrogen-doped C N fullerene are investigated using first-principles calculations. The calculations indicate that the C N fullerene is able to activate O molecules resulting in the formation of superoxide species ( O2-) both kinetically and thermodynamically. The active superoxide can further react with CO to form CO via the Eley-Rideal mechanism by passing a stepwise reaction barrier of only 0.20 eV. Ab initio molecular dynamics (AIMD) simulation is carried out to evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Besides, due to their curvature and pentagon defect compared with graphene, small porous nitrogen‐doped fullerenes have proven to exhibit rather high catalytic activity towards these reactions . A recent density functional theory (DFT) study by Lin and coworkers has shown that the incorporation of a nitrogen atom in C 60 , could greatly enhance the catalytic performance of this material towards the CO oxidation reaction. Chen and coworkers have also found that small N‐doped fullerenes C 59 N and C 39 N exhibit superior catalytic activity in the reduction of O 2 with energy barriers close to those on Pt (111).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Besides, due to their curvature and pentagon defect compared with graphene, small porous nitrogen‐doped fullerenes have proven to exhibit rather high catalytic activity towards these reactions . A recent density functional theory (DFT) study by Lin and coworkers has shown that the incorporation of a nitrogen atom in C 60 , could greatly enhance the catalytic performance of this material towards the CO oxidation reaction. Chen and coworkers have also found that small N‐doped fullerenes C 59 N and C 39 N exhibit superior catalytic activity in the reduction of O 2 with energy barriers close to those on Pt (111).…”
Section: Introductionsupporting
confidence: 80%
“…As evident, the spin density mostly accumulates over the carbon atom (C1) nearest to the nitrogen. According to the previous studies, such a large spin density over the mentioned site can considerably facilitate the adsorption of O 2 molecule and lower the reaction barriers for its catalytic reduction. Likewise, this atomic site is expected as the most active site to interact with the NO molecule, which will be discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…The bonding between O and C 59 B results in a charge transfer of approximately 0.86e (calculated using the Bader analysis technique 46 ) from C 59 B to O 2 to elongate the O-O bond by 0.19Å to activate the O 2 , which is close to previously reported results. 33,[47][48][49] In our calculation, the O 2 is found in the 3 S g À triplet ground state before adsorption onto C 59 B. When it gets close enough to C 59 B to adsorb onto it, a charge transfer would occur.…”
Section: Resultsmentioning
confidence: 65%
“…Chen and his co-workers reported DFT studies on CO oxidizations catalyzed by N doped C 60 (ref. 33) and penta-graphene. 34 In addition, B, N, P, and Si-doped graphene also shows superior reactivities for catalyzing CO oxidizations.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These structures are also well suited for use as a support in heterogeneous catalysis due to their huge specic area. [13][14][15] The ability to tune the electronic and surface properties of carbon-based nanomaterials by introducing defects or heteroatoms has shed light on their potential use in sensors and energy technologies. [16][17][18][19] Theoretical calculations [20][21][22] and experimental investigations, 23,24 for example, have demonstrated that N atoms may be effectively incorporated in different carbon materials, tailoring their chemical and electronic characteristics.…”
Section: Introductionmentioning
confidence: 99%